Abelia x grandiflora 'Sherwoodii' - Edward F. Gilman (EDIS, 2004)
This popular cultivar of glossy abelia is a fine-textured, semi-evergreen, small shrub with 1.5-inch-long, red-tinged leaves arranged along thin, stiff stems (Figure 1). Leaves and flowers are smaller than the species. It is much more compact than the species, resembling the Japanese or yaupon hollies. Considered to be evergreen in its southern range, glossy abelia will lose some of its leaves in colder climates, the remaining leaves taking on a more pronounced red color. Reaching a height of 3 to 6 feet with a spread of 6 to 10 feet, the mounded form of 'Sherwoodii' glossy abelia is clothed from spring through fall with terminal clusters of delicate pink and white, small, tubular flowers. This document is Fact Sheet FPS-003, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and and Agricultural Sciences, University of Florida. Publication date: October 1999; reviewed October 2003.